Factors Affecting the Security of Information Systems in Africa: A Literature Review - Lubua, Edison Wazoel; Semlambo, Adam Aloyce; Mkude, Catherine G (University of Dar es Salaam Library Journal, 2023)
This study determined factors affecting the security of Information Systems in Africa. Also, it established the quality of publications in the area of Information Security. The study is based on peer-reviewed publications conducted in Africa. The study adopted the mixed research approach. The study used a systematic literature review, with part of the analysis using descriptive analysis. In total, 70 papers formed the population of publications extracted in the area of Information Security. In addition, 37 papers had the quality to be included in the analysis of factors affecting Information Security. The study found that information Security factors are in four key categories: human factors, policy-related issues, work environment, and demographic factors. Overall, the work environment is the most reported category affecting the security of Information Systems in Africa. In addition, gender is the highest reported individual factor associated with the insecurity of Information Systems; female is the highly affected gender. Other factors include the lack of Information Security training, the unchecked level of trust, carelessness and poor security policies. The study recommends training programs, policy improvement and promoting behaviours that minimise exposure to attacks.